Okrogla miza ob 70-letnici ADP in njenega 7. člena - Gerbec, Franc (Pravnik, 2025)
On 8 May 2025, the Faculty of Law of the University of Ljubljana hosted a round table organised by the Association of Jurists’ Societies of Slovenia (ZDPS) and the Society for International Law for Slovenia, at the initiative of the ZDPS Legal Forum for Minorities. The event marked the 70th anniversary of the State Treaty on the Re-establishment of an Independent and Democratic Austria (AST) and, in particular, examined Article 7, which defines the rights of the Slovenian national community in Austrian Carinthia and Styria. Alongside the ZDPS President, Miha Juhart, PhD, and the Secretary of the Legal Forum for Minorities, Franci Gerbec, the panel comprised Vasilka Sancin, PhD, Lojze Ude, PhD, Rudi Vouk, mag. iur., Marco Jarc, and Attila Kovács, PhD. At the close of discussion, the participants adopted a statement proposing the creation of an institutionalised, permanent and constructive dialogue between the governments of the Republic of Slovenia and the Republic of Austria. This dialogue would include representatives of the autochthonous Slovenian minority in Austrian Carinthia and Styria, the governments of the relevant Austrian Länder, and experts from both countries. Its purpose would be to devise mechanisms and measures to ensure Austria’s full compliance with the AST - particularly Article 7, which guarantees the rights of the Slovenian minority in Austrian Carinthia and Styria. Slovenian jurists have expressed their readiness to assist in this endeavour, including through structured co-operation with their Austrian colleagues at all appropriate levels.
Keywords: Association of Jurists’ Societies of Slovenia; Austrian State Treaty; Avstrijska državna pogodba; Društvo za mednarodno pravo; Forum for Minorities; Forum za manjšine; narodne manjšine; national minorities; Slovenian language; slovenski jezik; Society for International Law; Zveza društev pravnikov Slovenije